2019
DOI: 10.3390/metabo9080167
|View full text |Cite
|
Sign up to set email alerts
|

Polar Lipids in Starch-Rich Commodities to be Analyzed with LC-MS-Based Metabolomics—Optimization of Ionization Parameters and High-Throughput Extraction Protocols

Abstract: Metabolomics-based approaches are still receiving growing attention with regard to food authenticity testing. Such studies require enormous sample numbers with negligible experimental or analytical variations to obtain statistically reliable results. In this context, an extraction protocol in line with optimized ionization parameters was developed in consideration of potential starch-derived matrix effects focusing on the polar lipids of potatoes. Therefore, well-known extractions (Bligh and Dyer, Folch, Matya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Results showed that the two approaches had no significant difference, which further proved the effectiveness of dichloromethane/methanol. A similar ratio of chloroform/methanol had also been reported suitable for lipidomic analysis of starch-rich samples in some previous publications [31,37]. Besides, different extracting periods (30 min, 60 min, and 120 min) were also compared in their efficiency of extracting non-polar components, and no visual difference was observed among all the three extracting periods, so the final extracting method was determined by using dichloromethane/methanol for 30 min.…”
Section: Optimization Of Analytical Methodsmentioning
confidence: 77%
See 1 more Smart Citation
“…Results showed that the two approaches had no significant difference, which further proved the effectiveness of dichloromethane/methanol. A similar ratio of chloroform/methanol had also been reported suitable for lipidomic analysis of starch-rich samples in some previous publications [31,37]. Besides, different extracting periods (30 min, 60 min, and 120 min) were also compared in their efficiency of extracting non-polar components, and no visual difference was observed among all the three extracting periods, so the final extracting method was determined by using dichloromethane/methanol for 30 min.…”
Section: Optimization Of Analytical Methodsmentioning
confidence: 77%
“…Dichloromethane/methanol (5/5, v/v ) showed the remarkable capability to extract as many metabolites as possible for wheat matrix compared with n-hexane and acetone/water (5/5, v/v ). This might be due to the fact that a combination of certain ratios of dichloromethane/methanol covered a large scale of polarity in the metabolites of wheat samples according to the “like dissolves like” rule [ 37 ]. In addition, single extraction by dichloromethane/methanol was also compared with the combination of three fractions consequently obtained from one QC sample ( Figures S1 and S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Some works were directed towards the identification of markers for characterization of food samples by its geographical origin in honey [57], garlic [14] or Adzuki Bean [30]; and for authentication of Protected Designation of Origin (PDO) of Grana Padano cheeses [56] and Colombian coffees [48]. Moreover, patterns of different agricultural practices were assessed in carrots [28], different varieties of legumes [26], potato [110], Vaccinium fruits [94] and almonds [111], as well as different species identity, geographical origin and production method of commercially prawn and shrimps [25]. The characterization of food products by untargeted approach was also determinant to prevent fraudulent practices, such as the production of adulterated fruit juices in citrus [89], the production of counterfeited Scotch Whisky [33], and dead on arrival instead of the typical slathered poultry meat [10].…”
Section: Food Processingmentioning
confidence: 99%
“…Thus, the visualization of only the products ions from a specific precursor is feasible, enhancing the purity of the MS 2 spectrum with the inherent benefits of DIA acquisitions regarding available MS/MS data for all future biomarkers. The potential of this technique has been recently evaluated for orange dietary biomarkers discovery [64] and implemented for comparison of different polar lipids extraction methods to be used in evaluation of botanical origin, with potatoes as a case of study [110]. In both studies, data processing was performed using Progenesis QI (Waters), a unique software, able of performing the processing of 4D data obtained with xC-IMS-HRMS instruments.…”
Section: Future Prospects and Conclusionmentioning
confidence: 99%